2003
DOI: 10.1161/01.cir.0000058164.68127.f2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Right Atrial Stretch on Atrial Electrical Remodeling in Patients With an Atrial Septal Defect

Abstract: Background-Adults with an atrial septal defect (ASD) frequently develop late atrial arrhythmias. We sought to characterize the pattern and persistence of atrial electrical remodeling caused by chronic right atrial (RA) stretch in this group. Methods and Results-Thirteen ASD patients without atrial arrhythmia (42Ϯ10 years old; RA volume, 65Ϯ16 mL) and 17 normal control subjects (44Ϯ11 years old; RA volume, 38Ϯ8 mL) had electrophysiological study to measure (1) atrial effective refractory period (AERP) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(52 citation statements)
references
References 37 publications
1
44
1
Order By: Relevance
“…Thus, one can only speculate about the possible mechanisms of new-onset atrial arrhythmias after patent foramen ovale closure, by which a deployed occlude device, potentially causes atrial fibrillation. Conduction delay at the atrial septum may persist beyond secundum ASD closure due to atrial septal stretching and may contribute to the long-term atrial arrhythmia substrate in this condition (18). The effects of acute stretch in studies have shown abnormal conduction slowing in response to atrial premature depolarization (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one can only speculate about the possible mechanisms of new-onset atrial arrhythmias after patent foramen ovale closure, by which a deployed occlude device, potentially causes atrial fibrillation. Conduction delay at the atrial septum may persist beyond secundum ASD closure due to atrial septal stretching and may contribute to the long-term atrial arrhythmia substrate in this condition (18). The effects of acute stretch in studies have shown abnormal conduction slowing in response to atrial premature depolarization (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, even in the absence of atrial arrhythmias, patients with conditions associated with atrial remodeling and atrial stretch (eg, congestive heart failure) exhibit altered SN function. [27][28][29][30][31] In clinical practice, prolongation of SN recovery time has been noted after conversion of atrial arrhythmias to sinus rhythm by electric cardioversion or catheter ablation. 32 Furthermore, patients with prolonged postcardioversion sinus pauses are more likely to experience AF recurrence after catheter ablation.…”
Section: Evidence For Link Between Snd and Afmentioning
confidence: 99%
“…Even many years after correction, this may result in conduction disturbances in the atrial myocardium. [22–26] According to Morton et al [27] , chronic right atrial stretch causes electrical remodeling with modest increases in the right atrial effective refractory period, and the right atrial remodeling persists after ASD closure and contributes to long-term atrial arrhythmia. Roberts-Thomson et al [28] also reported that ASDs are associated with chronic left atrial stretch, resulting in remodeling characterized by LA enlargement, loss of myocardium, and electrical scarring, which produce widespread conduction abnormalities, but do not lead to changes or increases in the effective refractory period.…”
Section: Discussionmentioning
confidence: 99%